Perkembangan Pendidikan Masa Daulah Abbasiyah - Farikhah, Iftitakhul; Astutik, Yuni; Ashari, M. Yahya (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2024)
The aim of writing this article is to discuss the progress of Islamic education during the Abbasid Dynasty. This research was carried out using the library method, namely looking for articles related to the topic. This type of research is library research using qualitative descriptive methods. The steps taken by researchers in reviewing this research include collecting sources from journals and books, commenting on sources, and writing up the results. The results of writing this article show that the development of Islamic education achieved rapid progress during the Abbasid Dynasty. This is shown by the many scientists who emerged in this era. Apart from that, there are also many educational institutions that have been established, including non-formal educational institutions and formal educational institutions.